Preterm Labour: prevalence and Possible Risk Factors - Rafid Abdulhaleem, Wasan (Open Journal of Physicians and Surgeons, 2026)
Background: Preterm deliveries are still high in underprivileged areas, which have led to high infant mortality and co-morbidity rates. Objectives: To measure prevalence of preterm birth at Al-Ameer private hospital and to identify factors associated with preterm delivery Methodology: A cross sectional study implemented in Labour ward of Al-Ameer private hospital in Baghdad city in one year duration from 1st of May, 2024 to 30th of April, 2025. The study population included all pregnant women admitted to the labour ward of the hospital for delivery and gave llive births (total 5850 pregnant women) during the index year. Preterm labour was defined as a live-birth before 37 completed weeks of gestation. Results: The prevalence of preterm labour in the hospital was (9.9%). The main detected risk factors of preterm birth were increased women's age, rural residency, multi-parity, lower educational level, previous induced labour, shorter interpregnancy interval, history of preterm labour, history of miscarriage, history of previous caesarean section, number of antenatal care visits, preeclampsia, newly diagnosed diabetes mellitus, medical illness, bleeding, premature rupture of membranes and oligohydraminous. The cesarean section was related to high incidence of prematurity. Conclusions: The prevalence of preterm birth in Al-Ameer private hospital is within acceptable range